Implementation of the Rubber Farmer Profit Sharing System in an Islamic Economic Perspective - Atika, Missi; Abidin, Zaenal; Yatima, Khusnul (Zabags International Journal of Economy, 2025)
This study aims to analyze the implementation of the profit-sharing system between rubber farmers and landowners in Parit Culum II Village from an Islamic economic perspective. The profit-sharing system is a common practice among rubber farmers; however, the application of justice principles in accordance with Islamic law is often questioned. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through direct interviews with farmers, landowners, and local community leaders. The findings indicate that the profit-sharing system applied is mostly in line with Islamic economic principles, such as justice, transparency, and deliberation. However, some practices need improvement, particularly in the aspect of initial agreements, which are often not formalized in writing. This study is expected to serve as a reference for improving a more equitable and Sharia-compliant profit-sharing system, thereby providing optimal benefits for all parties involved.